The Walls Have Ears: Accessing Participant Narratives amid Silence, Secrecy, and Mistrust (Medicine Anthropology Theory, 2021)
Eritreans have long been considered a close-knit community bound by the memorialisation of history and the preservation of cultural practices. My anthropological enquiry into the everyday experiences of mental distress among diasporic women revealed that the depth of their exclusivity was a response to the continual and unsystematic surveillance of the Eritrean state. Government spies targeted outspoken critics, either forcing them into exile or pushing them into perpetual silence. In this essay, I explain how the perceived looming presence of secret agents created widespread mistrust and pervasive silence that complicated relationship-building among diasporic women. I then describe how negative perceptions of the term ‘mental health’ required an alteration of my lexicon and methodological approach, revealing the embodiments of silence and distress in everyday interactions. By reflexively and critically engaging with women’s everyday experiences, silence emerges as a central theme in my work, eventually becoming a conceptual anchor that has helped me understand and connect with a politically silenced diaspora. Through these ethnographic encounters, the complexities of the social, cultural, and political interactions gave meaning to simple utterances.